Fine‐scale demographic processes resulting from multiple overseas colonization events of the Japanese stream tree frog, Buergeria japonica. (25th December 2016) - Komaki, Shohei; Lin, Si‐Min; Nozawa, Masafumi; Oumi, Shohei; Sumida, Masayuki; Igawa, Takeshi
Abstract: Aim: Amphibians are considered poor transoceanic dispersers because of their permeable skin. However, overseas dispersal of amphibian species has been revealed by recent phylogeographical studies and the role of overseas colonization of amphibians on their evolution and diversification has also been highlighted. However, no studies have investigated in detail the demographic processes related to these overseas colonization events. To clarify how amphibians achieve overseas colonization, we estimated the demographic history of the Japanese stream tree frog, Buergeria japonica, which is distributed on Amami Island and four northern neighbouring islands of the Tokara Archipelago, Japan. Location: South‐western islands of Japan and Taiwan. Methods: We analysed the mitochondrial cytb gene and 20 microsatellite loci, and constructed phylogenetic trees based on these data. We also performed demographic analyses by applying approximate Bayesian computation (ABC) method and an isolation‐with‐migration model. Results: Phylogenetic and demographic analyses based on cytb and 20 microsatellite genotype data revealed that divergence among island populations took place recently, mostly within the last few thousand years. Populations from the northern islands had reduced genetic diversity compared with southern islands, and ABC analyses supported the hypothesis that the species colonized islands from south to north. Main conclusions: Given that the islands are separated from each other by deep sea, the recent divergences observed indicate overseas colonization events among the five islands. ABC analyses support the hypothesis that B. japonica underwent a stepping‐stone overseas colonization from southern to northern neighbouring islands during the past few thousand years accompanied by multiple founder effects. These results support the hypothesis that overseas colonization could have had a substantial impact on amphibian evolution and diversification.